Key technology development needs and applicability analysis of renewable energy hybrid technologies in off-grid areas for the Rwanda power sector. Issue 1 (January 2020) - Niyonteze, Jean De Dieu; Zou, Fumin; Norense Osarumwense Asemota, Godwin; Bimenyimana, Samuel; Shyirambere, Gilbert
Abstract: Until recently, the Rwanda power sector increased rapidly to double the 2010 installed capacity. The energy consumption in Rwanda experienced a steady rise correspondingly with the population and modern socio-economic life. Consequently, Rwanda household access to electricity increased to 53% by September 2019. Not only does 47% of Rwanda's population lack electricity access, there are persistent power failures and the grid is also unstable. Using renewable energy hybrid technologies in off-grid areas might be a solution to this problem. However, the high cost of renewable energy hybrid systems has led to its slow adoption in many developing countries. Hence, it is important to find the most appropriate hybrid combinations that reduce energy cost and access electricity generation that maximizes the available renewable energy resources. This paper examines some new technology development needs related to the power sector in Rwanda. Secondly, four different 100% renewable energy hybrid systems were designed and simulated to support rural and remote areas considering an average load demand of 158.1 kWh/day with a peak load of 18 kW. The hybrid systems simulation and optimization were obtained using HOMER (hybrid optimization model for electric renewables) software. The input data were obtained from National Aeronautics and Space Administration (NASA) for solar and wind resources, and hydro resources were from real-time field data for selected study site. The simulation results indicate hydro/solar/battery hybrid is the most cost-effective and environmentally viable alternative for off-grid rural electrification because of low net present cost (NPC) and least greenhouse gas emissions. The proposed hybrid combination could apply to other rural areas in the region and elsewhere in the world especially where climate conditions are similar. Abstract : Energy, Electrical engineering, Off-grid rural electrification, Renewable energy, Hybrid systems, HOMER, Rwanda.